Entrenador nuevo, ¿victoria segura? Evidencia en baloncesto - Martinez, J. A. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2012)
This research shows that a widespread social wisdom in sports: "change the coach, guarantee the win" has an empirical basis. Obviously, this type of saying is not fully met in all the games, but the evidence derived from the analysis of changes of coaches along the NBA history reveals that the probability of winning increases in the first game managed by a new coach. Through the analysis of logit models, results show that the probability of winning a game for the first game piloted by a new coach is about 2 times higher than the probability of winning the game before the change has occurred. Implications related to variables such as home/field advantage or the quality of teams are discussed.